Prickly Ash Seeds improve immunity of Hu sheep by changing the diversity and structure of gut microbiota - Li, Dengpan; Yang, Hai; Li, Qiao; Ma, Keyan; Wang, Huihui; Wang, Chunhui; Li, Taotao; Ma, Youji (Frontiers in Microbiology, 2023)
Prickly Ash Seeds (PAS), as a traditional Chinese medicinal herb, have pharmacological effects such as anti-asthma, anti-thrombotic, and anti-bacterial, but their impact on gut microbiota is still unclear. This study used a full-length 16s rRNA gene sequencing technique to determine the effect of adding PAS to the diet on the structure and distribution of gut microbiota in Hu sheep. All lambs were randomly divided into two groups, the CK group was fed with a basal ration, and the LZS group was given a basal diet with 3% of PAS added to the ration. The levels of inflammatory factors (IL-10, IL-1β and TNF-α) in intestinal tissues were measured by enzyme-linked immunosorbent assay (ELISA) for Hu sheep in the CK and LZS group. The results indicate that PAS can increase the diversity and richness of gut microbiota, and can affect the community composition of gut microbiota. LEfSe analysis revealed that Verrucomicrobiota, Kiritimatiella, WCHB 41, and uncultured_rumen_bacterium were significantly enriched in the LZS group. KEGG pathway analysis found that LZS was significantly higher than the CK group in the Excretory system, Folding, sorting and degradation, and Immune system pathways (P < 0.05). The results of ELISA assay showed that the level of IL-10 was significantly higher in the LZS group than in the CK group (P < 0.05), and the levels of TNF-α and IL-1β were significantly higher in the CK group than in the LZS group (P < 0.05). LEfSe analysis revealed that the dominant flora in the large intestine segment changed from Bacteroidota and Gammaproteobacteria to Akkermansiaceae and Verrucomicrobiae after PAS addition to Hu sheep lambs; the dominant flora in the small intestine segment changed from Lactobacillales and Aeriscardovia to Kiritimatiellae and WCHB1 41. In conclusion, the addition of PAS to sheep diets can increase the number and types of beneficial bacteria in the intestinal tract, improve lamb immunity, and reduce intestinal inflammation. It provides new insights into healthy sheep production.